Trust we lost: The impact of the Treuhand experience on political alienation in East Germany - Kim Leonie Kellermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Do politically administered mass layoffs undermine trust and political interest? During the German reunification, formerly state-owned socialist firms in East Germany were privatized by the Treuhand, which came at the cost of massive job losses and public protest. I demonstrate that these activities had a detrimental effect on attitudes and political behavior of the affected individuals. Using survey data from the German Socio-economic Panel and election results, I find that East Germans who lost their jobs exhibit significantly lower trust levels, lower political interest and a lower identification with mainstream democratic parties, even up to 30 years after reunification. I corroborate the causality of the results using fixed-effects estimations and a placebo analysis, which fails to explain political disenchantment by reasons other than the Treuhand experience. I interpret the findings as the persistent, negative effect of perceived political mismanagement during a crucial phase of economic transition on long-run political identification.
Keywords: D72; E24; L33; 330; East Germany; trust; political alienation; privatization; radical voting